(untitled) (Proceedings of the Society of Antiquaries of Scotland, 1865)
A description of the ruins of the Church of St Mary’s in Cambuskenneth and the church’s history. The article is primarily a report on the excavation that took place in 1864 to discover the whereabouts of the tombs of James III and his Queen, Margaret of Denmark. The excavators found what they presumed to be the remains of the two monarchs and their child. The article also contains discussion of the finds and architectural features that were uncovered during the excavation. After the communication was read, there was some discussion of the contents among the attendees.